White matter hyperintensities and late-life cognition: an analysis of moderation effects of mild behavioral impairment - Duan, Jiayu; Wang, Ningqun; Li, Shixin; Wang, Yefei; Song, Jiale; Li, Xiaoshan; Guo, Jingrui; Liao, Junya; Wang, Yihan; Zhang, Ying; Zhang, Yunling; Jin, Xianglan (Frontiers in Aging Neuroscience, 2026)
BackgroundMild behavioral impairment (MBI) is recognized as a potential early marker for dementia and may be indicative of the increased risk in the predementia stage. This study investigated whether MBI could moderate the impact of white matter hyperintensities (WMHs) on late-life cognitive function in patients with arteriosclerotic cerebral small vessel disease (aCSVD).MethodsPatients were categorized into two groups based on Fazekas scores: low WMH burden (LWMH, scores 1–2; n = 119) and high WMH burden (HWMH, scores 3–6; n = 110). Logistic regression analysis was used to assess the associations among WMH, MBI, and screen-positive cognitive impairment. Moderation analysis was conducted to evaluate whether the presence of MBI could influence the relationship between WMH and cognitive outcomes.ResultsWMH was associated with MBI (p < 0.001) and screen-positive cognitive impairment (MoCA: p = 0.003; MMSE: p = 0.025), and MBI was correlated with screen-positive cognitive impairment (p = 0.010 and 0.007, respectively). HWMH was independently correlated with screen-positive cognitive impairment and MBI (p = 0.001; p < 0.001; p = 0.031). Compared with cases in the non-MBI group, those in the MBI group had more WMHs in the occipital lobes (p = 0.016) and subcortical structures (p = 0.042). Furthermore, MBI significantly moderated the association between WMH and screen-positive cognitive impairment (β = −0.10, p < 0.014; β = −0.06, p < 0.041).ConclusionThe presence of MBI may exacerbate the cognitive decline associated with WMH in patients with aCSVD. These findings highlight the importance of early identification and monitoring of MBI in cases with WMH to better assess dementia risk and to develop interventional strategies.